The Moderating Role of Online Awareness in the Association between Strategy Use and Performance Accuracy on a Test of Functional Cognition in Individuals with Acquired Brain Injury - Salazar-Frías, Daniel; Funes, Maria Jesus; Szot, Ana Clara; Laffarga, Lucia; Navarro-Egido, Alba; Rodriguez-Bailon, Maria (Oxford Academic, 2024)
Objective: Deficits in online self-awareness (SA) are common after acquired brain injury (ABI), leading to safety concerns and impacting daily activities and rehabilitation outcomes. Early identification is recommended as a critical first step in cognitive rehabilitation following ABI. The aim of this observational study was to examine differences in online SA and strategy use between individuals with ABI and healthy controls. It also investigated whether online SA moderates the relationship between strategy use and performance accuracy on a test designed to assess cognitive-functional deficits. Method: 80 individuals with ABI and 76 controls completed the Spanish Weekly Calendar Planning Activity-10. Measures of online SA included strategy use and self-recognized errors assessed during task. An after-task interview assessed individuals’ self-evaluation of task difficulty and accuracy of performance. Results: Individuals with ABI performed worse than controls on most measures of online SA. They were less likely to self-recognize errors and use self-monitoring strategies. They also tended to overestimate their performance and showed greater discrepancy between self-rated and actual performance. Moderation analyses show that better performance was significantly associated with greater strategy use among ABI individuals who were aware of their performance. Conclusions: Online SA appears to moderate the use of cognitive strategies during functional cognitive performance after ABI. Therefore, it is important to include assessments of online SA and strategy use for individuals with ABI. Furthermore, these findings highlight the importance of focusing on SA and self-generated strategies as key goals of cognitive rehabilitation aimed at improving daily functioning after ABI.
Keywords: Isquemia cerebral - Fisioterapia; Acquired brain injury; Online awareness; Everyday functioning; Cognitive rehabilitation; Cognitive strategies; Neuropsychology; Cognitive assessment